Research of theoretical basis of business model quality management of restaurant business entity - Grosul, Victoria; Ivanova, Tatyana (Technology audit and production reserves, 2017)
The key points of «quality management» concept (as management function, management process and a system of evaluation of management activities) are identified on the basis of critical analysis of invariant interpretations of its essence These characteristics indicate the complexity of «quality control» concept and the ambiguity of its contents. Based on a synthesis of existing approaches to the interpretation of the essence of «quality management» concept including industry features of restaurant business entity, its basic essential features are defined (aim of management, objectives, object, subject, methods and means of management, functional orientation, time lag, value priorities) and the author’s vision of the contents of «business model quality management of restaurant business entity» is formulated as a coordinated activity that is controlling the value propositions (range, food sales concept, service level), key partners, consumer segments, key resources, cost structure, relationships with customers, revenue streams. Trends of development of explored «quality control» concept and general management are investigated to determine the preferred approach to building a quality management system of enterprise business model. It is proved that quality improvement of enterprise business model is based on an innovative approach to management at all stages of production, distribution, exchange and consumption.